Human oocyte capacitation culture: Essential step toward hormone‐free assisted reproductive technology - Johan Smitz; Flor Sánchez; Sergio Romero; Heidi Van Ranst; Ellen Anckaert; Robert B. Gilchrist; Tuong M. Ho; Lan N. Vuong; Yoshiharu Morimoto (Reproductive Medicine and Biology)
Abstract Background In vitro oocyte maturation (IVM) is not a novel concept; however, its wide‐scale practice has been limited because of the lower clinical outcomes compared to conventional assisted reproductive technologies. Methods This comprehensive review addresses the significant advances made in oocyte in vitro maturation with the biphasic capacitation (CAPA)‐IVM strategy applied to small ovarian antral follicles in humans over the last 10 years. CAPA‐IVM consists of a prematuration phase wherein immature oocytes are temporarily meiotically arrested to gain competence before undergoing meiotic resumption. Main findings The integration of knowledge from basic research in animal models into clinical practice has led to a reevaluation of IVM for policystic ovary syndrome (PCOS) and onco‐fertility patients. The introduction of meticulously conceived growth factors, hormonal supplements, and culture conditions led to an integrated biphasic CAPA‐IVM system that promotes oocyte competence. A series of prospective randomized controlled studies validated the reproducible improvements in clinical outcomes and the safety of CAPA‐IVM. So far, nearly 1000 babies have been born using this approach. Conclusion The use of CAPA‐IVM in clinical studies has set the tone for major progress in the field and is achieving a safer, less expensive, and less emotionally loaded IVF experience, currently validated for PCOS patients.